Exploring Bacterial Carboxylate Reductases for the Reduction of Bifunctional Carboxylic Acids. Issue 11 (5th September 2017) - Khusnutdinova, Anna N.; Flick, Robert; Popovic, Ana; Brown, Greg; Tchigvintsev, Anatoli; Nocek, Boguslaw; Correia, Kevin; Joo, Jeong C.; Mahadevan, Radhakrishnan; Yakunin, Alexander F.
Abstract : Carboxylic acid reductases (CARs) selectively reduce carboxylic acids to aldehydes using ATP and NADPH as cofactors under mild conditions. Although CARs attracts significant interest, only a few enzymes have been characterized to date, whereas the vast majority of CARs have yet to be examined. Herein the authors report that 12 bacterial CARs reduces a broad range of bifunctional carboxylic acids containing oxo‐, hydroxy‐, amino‐, or second carboxyl groups with several enzymes showing activity toward 4‐hydroxybutanoic (4‐HB) and adipic acids. These CARs exhibits significant reductase activity against substrates whose second functional group is separated from the carboxylate by at least three carbons with both carboxylate groups being reduced in dicarboxylic acids. Purified CARs supplemented with cofactor regenerating systems (for ATP and NADPH), an inorganic pyrophosphatase, and an aldo‐keto reductase catalyzes a high conversion (50–76%) of 4‐HB to 1, 4‐butanediol (1, 4‐BDO) and adipic acid to 1, 6‐hexanediol (1, 6‐HDO). Likewise, Escherichia coli strains expressing eight different CARs efficiently reduces 4‐HB to 1, 4‐BDO with 50–95% conversion, whereas adipic acid is reduced to a mixture of 6‐hydroxyhexanoic acid (6‐HHA) and 1, 6‐HDO. Thus, our results illustrate the broad biochemical diversity of bacterial CARs and their compatibility with other enzymes for applications in biocatalysis. Abstract : Carboxylic acid reductases (CAR) reduce carboxylic acids to aldehydes using ATP and NADPH as cofactors. In this work, the authors demonstrated that 12 bacterial CARs can reduce a broad range of bifunctional carboxylic acids. Several CARs catalyzed a high conversion of 4‐hydroxybutanoic and adipic acids to 1, 4‐butanediol, 1, 6‐hexanediol, and 6‐hydroxyhexanoic acid in vitro (in combination with cofactor regenerating systems and aldo‐keto reductases) and in vivo (in E. coli cells).